FAKTOR-FAKTOR PERINGANAN HUKUMAN DALAM UNDANG-UNDANG ISLAM DAN UNDANG-UNDANG SIVIL - Mustapha, Ahmad Sharifuddin; Mehat, Hashim; Mohamed Shith, Mohd Sirajuddin; Mohamad, Zulkifli; Salleh, Ahmad (Journal of Techno-Social, 2012)
Punishment is one of the last process in a trial in which the court decision or judgment will be made by the judiciary against offenders after conviction does. However, in certain situations punishment be mitigated or dropped. To enable the mitigating there are several factors that must be available on the offenders. This article will discuss mitigating factors of punishment in Islamic law and civil law as well as peeling and make comparisons between them. In addition, also included cases that had been tried in the early days of Islam and also cases that have been decided in the courts of Malaysia, Singapore and so on.